2013
DOI: 10.1155/2013/573051
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Sulfur Dioxide from Flue Gas Using the Sludge Sodium Humate

Abstract: This study shows the ability of sodium humate from alkaline treatment sludge on removing sulfur dioxide (SO2) in the simulated flue gas. Experiments were conducted to examine the effect of various operating parameters, like the inlet SO2 concentration or temperature or O2, on the SO2 absorption efficiency and desulfurization time in a lab-scale bubbling reactor. The sludge sodium humate in the supernatant after alkaline sludge treatment shows great performance in SO2 absorption, and such efficiency can be main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Na 2 SO 3 þ H 2 O). [51] Since most fossil-fuel-based power plants and oil refineries are regulated to emit ultralow levels of SO 2 gas, massive amounts of Na 2 SO 3 are readily available, indicating the promising viability of SOR for solar-driven hydrogen generation. [50] Additionally, SOR leaves behind Na 2 SO 4 as a byproduct.…”
Section: Resultsmentioning
confidence: 99%
“…Na 2 SO 3 þ H 2 O). [51] Since most fossil-fuel-based power plants and oil refineries are regulated to emit ultralow levels of SO 2 gas, massive amounts of Na 2 SO 3 are readily available, indicating the promising viability of SOR for solar-driven hydrogen generation. [50] Additionally, SOR leaves behind Na 2 SO 4 as a byproduct.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the temperature increasing causes adsorbent to be easier to adsorb [23]. The higher the temperature the viscosity of crude oil decreaseand sulfur rings will molecule into smaller rings then simple compounds were formed then these rings are easily broken, making the removal efficiency high [24].as (Basfar et al 2012) reported that DBT converted to H 2 S at high temperature [25].while (Yu Zhao et al 2013) reported the reason of increase removal efficiency when temperature increased due to decrease of sulfur solubility and that made its removal easy.Also at high-temperature crude oil viscosity decreaseand its molecule's speed was increase and contact time between crude oil molecules and sulfur molecules was decreasetoo [26].…”
Section: 3-temperature Effectmentioning
confidence: 99%
“…In addition to coal HA−Na derived from low quality coal, SHA−Na solution was also designed to remove SO 2 from flue gas. Zhao et al 28 proposed a scheme of application of the SHA−Na for FGD ( Figure 3) and studied the ability of HA−Na from alkaline treatment sludge on removing SO 2 . The SHA−Na shows great performance in SO 2 absorption, and 98% desulfurization efficiency can be achieved under optimum operating conditions, while the highest sulfur capability is 0.037 g (SO 2 )/g (SHA−Na) in the process.…”
Section: Application Of Ha In Waste Gas Treatmentmentioning
confidence: 99%